Kyrgyz Republic : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2016)
External shocks continue to shape both the outlook and policies. A weaker-than-expected external environment is hurting growth, straining the budget, and raising public debt and banking sector vulnerabilities. The authorities' response to shocks has focused on exchange rate flexibility and unorthodox stimulus measures, although the budget deficit in 2015 was well within the program target. For 2016, the authorities are undertaking additional efforts to adhere to the program's fiscal commitments. Financial sector vulnerabilities and risks are high and rising. Slow progress toward passing the Banking Law that aims to introduce a modern bank resolution system and increase the independence of the National Bank of the Kyrgyz Republic remains a concern. The change in the cabinet just six months after the elections underlines the fluidity of the country's political situation.